Composite reinforcements for optimum performance - Boisse, Philippe (Woodhead Publishing series in composites science and engineering., 2011)
Reinforcements are an integral part of all composites and the quality and performance of the composite can be optimised by modelling the type and structure of the reinforcement before moulding. Composite reinforcements for optimum performance reviews the materials, properties and modelling techniques used in composite production and highlights their uses in optimising performance. Part one covers materials for reinforcements in composites, including chapters on fibres, carbon nanotubes and ceramics as reinforcement materials. In part two, different types of structures for reinforcements are discussed, with chapters covering woven and braided reinforcements, three-dimensional fibre structures and two methods of modelling the geometry of textile reinforcements: WiseTex and TexGen. Part three focuses on the properties of composite reinforcements, with chapters on topics such as in-plane shear properties, transverse compression, bending and permeability properties. Finally, part four covers characterising and modelling of reinforcements in composites, with chapters focusing on such topics as microscopic and mesoscopic approaches, X-ray tomography analysis and modelling reinforcement forming processes. With its distinguished editor and international team of contributors, Composite reinforcements for optimum performance is an essential reference for designers and engineers in the composite and composite reinforcement manufacturing industry, as well as all those with an academic research interest in the subject. Reviews the materials, properties and modelling techniques used in composite production and highlights their uses in performance optimisationCovers materials for reinforcements in composites, including fibres, carbon nanotubes and ceramicsDiscusses characterising and modelling of reinforcements in composites, focusing on such topics as microscopic and mesoscopic approaches, X-ray tomography analysis and modelling reinforcement forming processes.